Motivations, expectations, and benefits in relation to trade show attendance of third year BSID - Senador, Bianca Colleen T.
The study aimed to determine why third year students of the BS Interior Design program of the University of the Philippines attend local design and construction trade shows, their expectations from these trade shows, and what they gained from their attendance. Survey was the data collection method of the study. There were twenty- five (25) respondents composed of third year BSID students, selected through purposive sampling. The instrumentation used in the study are survey questionnaire and tally sheets. Quantitative and qualitative methods were used to analyze the survey data. Results show that the respondents were motivated to attend local design and construction trade shows because of the prospect of seeing new products and interesting exhibit showcases and meeting well-known personalities. Other factors that influenced their attendance were the venue of the trade show, the price of entrance fees and the mode of transportation going to and from the venue. The expectations of the students revolved around three (3) aspects of the trade show namely, the exhibit design and products, innovation and novelty, and the design showcase. The respondents recognized the benefits that they gained from their attendance which include new and inspiring ideas in design, a broader knowledge in materials, and networking. The motivating factors that encouraged the respondents to attend trade shows as well as their expectations were influenced by their desire to be updated with the current trends in the design industry. Furthermore, the benefits they gained from their attendance did not only meet their expectations, it had also been incorporated into various design courses specifically those dealing with furniture design and materials.